Nucleotide Sequencing and SNP Detection of Toll-Like Receptor-4 Gene in Murrah Buffalo (Bubalus bubalis) - Mitra, M. (ISRN Mol Biol, 2012)
Toll-like receptor-4 (TLR-4) has an important pattern recognition receptor that recognizes endotoxins associated with gram negative bacterial infections. The present investigation was carried out to study nucleotide sequencing and SNP detection by PCR-RFLP analysis of the TLR-4 gene in Murrah buffalo. Genomic DNA was isolated from 102 lactating Murrah buffalo from NDRI herd. The amplified PCR fragments of TLR-4 comprised of exon 1, exon 2, exon 3.1, and exon 3.2 were examined to RFLP. PCR products were obtained with sizes of 165, 300, 478, and 409 bp. TLR-4 gene of investigated Murrah buffaloes was highly polymorphic with AA, AB, and BB genotypes as revealed by PCR-RFLP analysis using Dra I, Hae III, and Hinf I REs. Nucleotide sequencing of the amplified fragment of TLR-4 gene of Murrah buffalo was done. Twelve SNPs were identified. Six SNPs were nonsynonymous resulting in change in amino acids. Murrah is an indigenous Buffalo breed and the presence of the nonsynonymous SNP is indicative of its unique genomic architecture. Sequence alignment and homology across species using BLAST analysis revealed 97%, 97%, 99%, 98%, and 80% sequence homology with Bos taurus, Bos indicus, Ovis aries, Capra hircus, and Homo sapiens, respectively.